Cross sectional study of sensorineural hearing loss in type 2 diabetes mellitus - Makwana, Abhijit V.; Sharma, Pratik; Vyas, Shifa; Nahar, Rahul; Singh, Maya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The objective of the study was to evaluate the prevalence of sensorineural hearing loss in type 2 diabetes mellitus and to figure out a relation between age, sex, duration of diabetes and diabetic control. Methods: A cross-sectional study was conducted at Geetanjali Medical College and Hospital for 1.5 years. Patients were known case of diabetes mellitus type 2 without any other systemic illness included in the study. A total of 115 patients were involved in the study and the informed consent was taken. A detailed examination and history related to hearing loss and diabetes status with treatment was elicited. All basic blood investigations were performed on all the patients. All the patients were subjected to pure tone audiometry and impedance audiometry in a sound proof room. Results: The total prevalence of sensorineural hearing loss in the study subjects was found to be 80% with most of them having mild degree of sensorineural deafness. Increase in age, longer duration and uncontrolled diabetes are the factors which had higher risk of developing sensorineural hearing loss in the study subjects. Conclusions: There is a strong association between sensorineural hearing loss and duration of diabetes mellitus-2. The threshold of hearing loss is increased mainly at the higher frequencies with diabetes.